Influence of timing of delayed hard palate closure on articulation skills in 3‐year‐old Danish children with unilateral cleft lip and palate. Issue 1 (25th July 2017) - Willadsen, Elisabeth; Boers, Maria; Schöps, Antje; Kisling‐Møller, Mia; Nielsen, Joan Bogh; Jørgensen, Line Dahl; Andersen, Mikael; Bolund, Stig; Andersen, Helene Søgaard
Abstract: Background: Differing results regarding articulation skills in young children with cleft palate (CP) have been reported and often interpreted as a consequence of different surgical protocols. Aims: To assess the influence of different timing of hard palate closure in a two‐stage procedure on articulation skills in 3‐year‐olds born with unilateral cleft lip and palate (UCLP). Secondary aims were to compare results with peers without CP, and to investigate if there are gender differences in articulation skills. Furthermore, burden of treatment was to be estimated in terms of secondary surgery, hearing and speech therapy. Methods & Procedures: A randomized controlled trial (RCT). Early hard palate closure (EHPC) at 12 months versus late hard palate closure (LHPC) at 36 months in a two‐stage procedure was tested in a cohort of 126 Danish‐speaking children born with non‐syndromic UCLP. All participants had the lip and soft palate closed around 4 months of age. Audio and video recordings of a naming test were available from 113 children (32 girls and 81 boys) and were transcribed phonetically. Recordings were obtained prior to hard palate closure in the LHPC group. The main outcome measures were percentage consonants correct adjusted (PCC‐A) and consonant errors from blinded assessments. Results from 36 Danish‐speaking children without CP obtained previously by Willadsen in 2012 were used for comparison. Outcomes & Results: Children with EHPC produced significantly more target consonants correctly (83%) than children with LHPC (48%; p < .001). In addition, children with LHPC produced significantly more active cleft speech characteristics than children with EHPC ( p < .001). Boys achieved significantly lower PCC‐A scores than girls ( p = .04) and produced significantly more consonant errors than girls ( p = .02). No significant differences were found between groups regarding burden of treatment. The control group performed significantly better than the EHPC and LHPC groups on all compared variables.